Pengaruh Kompensasi, Disiplin Kerja dan Motivasi terhadap Produktivitas Kerja Karyawan PT. Sekar Katokichi Sidoarjo - Mariani, Diana Santi Putri; Firdaus, Vera (Indonesian Journal Publisher, 2024)
The research aims. To determine the effect of compensation, work discipline and motivation on the work productivity of PT. Sekar Katokichi Sidoarjo. The approach used. In this research is a quantitative approach. The population in this study was 300 employees. Sampling techniques using proportional stratified random sampling techniques. Samples in this study were 172 respondents. Analysis Using SPSS Software.The results of this study indicate that partially and simultaneously compensation, work discipline and motivation affect the work productivity of PT. Sekar Katokichi's employees.